Cessation of Continuous Flow Left Ventricular Assist Device–Related Gastrointestinal Bleeding After Heart Transplantation. Issue 2 (March 2018) - Patel, Snehal R.; Oh, Kyung Taek; Ogriki, Tolulope; Sims, Daniel; Shin, J. Julia; Madan, Shivank; Saeed, Omar; Goldstein, Daniel J.; Jorde, Ulrich P.
Abstract : Gastrointestinal bleeding (GIB) is a major complication of continuous flow left ventricular assist device (CF LVAD) therapy. The precise pathophysiology of CF LVAD–related bleeding remains poorly understood, and the effect of pump removal at the time of transplantation on actual bleeding frequency has not previously been studied. A single-center retrospective review was conducted on patients who received CF LVAD and subsequently developed GIB. Baseline demographics and markers of pulsatility (aortic valve opening and the HeartMate II [HM2] pulse index) were compared between those with and without GIB. In those patients who had GIB and proceeded to heart transplantation, the frequency and etiology of recurrent GIB post-transplant was assessed. A total of 88 GIBs occurred in 54 of 214 patients who received CF LVAD implantation (25%, 0.36 events per patient-year). Median time to first bleeding was 65 (interquartile range [IQR]: 37–229) days, and arteriovenous malformation (AVM) was the etiology in 36% of all episodes. On multivariate analysis, age (odds ratio [OR]: 1.05; 95% confidence interval [CI]: 1.01–1.09; p = 0.006) and HM2 pulse index (OR: 0.57; 95% CI: 0.35–0.90; p = 0.017) were significantly associated with GIB. There were 28 patients who had at least one GIB event during LVAD support and proceeded to transplant. None of these patients had recurrent bleeding after heart transplantation. This is the first documentation that transplantation effectively eliminates CF LVAD–related GIB. Current guidelines recommending prioritization for transplant for patients who develop recurrent GIB after CF LVAD are justified.